SUAP MENYUAP DAN MAFIA PERADILAN DI INDONESIA : TELAAH KRIMINOLOGIS - Muhammad Mustofa (Masalah-Masalah Hukum, 2013)
Abstract This article addresses the bribery case that involved high ranking of Indonesian Officials of various branch in Indonesian Political System. A Judge of Supreme Court, a Member of Parliament, an Attorney, and Police Officers may involve in the conspiracy that breached the system. The high rank of bribery maight be present when tehere is lack of control and supervision in beaurocracy because beaurocracry is monopoly type of services function by govermental organisation. Keywords : bribery, supervision in beaurocracy Abstrak Artikel ini membahas kasus-kasus suap menyuap yang melibatkan para petinggi dalam Sistem Politik Indonesia. Ia dapat melibatkan seorang Hakim Agung, Anggota DPR, Jaksa dan Polisi. Suap-menyuap tingkat tinggi dapat terjadi apabila terdapat kelemahan dalam pengendalian dan pengawasan birokrasi, karena birokrasi pada dasarnya adalah fungsi pelayanan pemerintahan yang bersifat monopolistik. Kata Kunci : suap-menyuap, pengawasan birokrasi